Towards the next generation of solid oxide fuel cells operating below 600 °c with chemically stable proton-conducting electrolytes - Fabbri, Emiliana (Advanced materials (Deerfield Beach, Fla.), 2012)
Copyright © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.